Competition of velvetleaf (Abutilon theophrasti M.) weed with cotton (Gossypium hirsutum L.). Economic damage threshold - Cortés, J. A.; Mendiola, M. A.; Castejón, M. (Spanish Journal of Agricultural Research, 2010)
The effect of the weed Abutilon theophrasti M. (common name: velvetleaf) on the growth of cotton grown in the Guadalquivir Valley, was studied by examining the influence of weed density on growth of the weed and that of cotton. Velvetleaf impeded normal cotton growth caused production losses as a result of the stress the cotton was subjected to. Additionally there was competition among velvet leaf plants at high velvet leaf densities. The influence of velvetleaf density in coexistence with cotton has been also studied evaluating weed effect on the biomass of cotton and its production. Additional determinations included the velvetleaf seed production capacity per unit area and seed production per plant. These determinations were adjusted to hyperbolic, inverse linear and logistic models. Last, the economic damage threshold (EDT) was calculated using the efficiency level in control of velvetleaf in cotton. In this calculation the treatment cost and losses caused by the weed, in the crop, were taken into account. The EDT varied between 0.1 and 0.5 velvetleaf plant m-2, depending on the control methods used.